Fiscal policy and growth: do financial crises make a difference? - António Afonso; Hans Peter Grüner; Christina Kolerus (European Central Bank (ECB), 2010)
In this paper we assess to what extent in the existence of a financial crisis, government spending can contribute to mitigate economic downturns in the short run and whether such impact differs in crisis and non crisis times. We use panel analysis for a set of OECD and non-OECD countries for the period 1981-2007. The fiscal multiplier for the full sample for instrumented regular and crisis spending is about 0.6-0.8 considering the sample average government spending share of GDP of about one third. Altogether, we cannot reject the hypothesis that crisis spending and regular spending have the same impact using a variation of controls, sub-samples and specifications.
Keywords: C23; E62; E44; F43; H50; 330; EU; financial crisis; Fiscal Policy; Growth; oecd; panel analysis; Finanzpolitik; Finanzkrise; Wirtschaftswachstum; EU-Staaten; Panel; OECD-Staaten